Impact of the Implementation of a New Information System in the Management of Higher Education Institutions (2018)
Those responsible for management in Higher Education Institutions require real-time Information Systems, which provide reliable and well-presented information, while helping them in this management and in decision-making. The financial information, emanated from these Systems, becomes a basic input, since the financial results of a company now become the most used and relevant reference of the actions of its leaders. In this article, we present the different Modules that are used for university management, Modules that have an Information System in their administrative and financial component ―Budgets, Financial Accounting, Treasury, Payroll, Purchases, Inventory, Payments― and, also it describes the most outstanding functionalities of each Module. In order to determine the impact of the implementation of the System in the Corporacion Universitaria del Caribe— CECAR, the metrics of the ISO/IEC 25010 quality model are used, in terms of the achievement of each User, to determine the effectiveness, efficiency, satisfaction, utility and flexibility. The results show the impact of the System on the administrative and financial dynamics of the Institution